Impact of Lycium barbarum arabinogalactan on the fecal metabolome in a DSS-induced chronic colitis mouse model. Issue 16 (1st August 2022) - Cao, Cui; Wang, Linlin; Ai, Chunqing; Gong, Guiping; Wang, Zhongfu; Huang, Linjuan; Song, Shuang; Zhu, Beiwei
Abstract : Gut microbes and untargeted/targeted metabolomics were combined to comprehensively understand the therapeutic effect and the underlying mechanism of Lycium barbarum arabinogalactan (LBP-3) in DSS-induced colitis mice. Abstract : Ulcerative colitis (UC) is often accompanied by the dysbiosis of gut microbiota and metabolism. Our previous study indicated that arabinogalactan from Lycium barbarum (LBP-3) could markedly attenuate the symptoms of chronic UC in mice by modulating the structure of gut microbiota. This study explored the impact of LBP-3 on the fecal metabolomic profiling of the same cohort of mice by HPLC-TripleTOF/MS. Untargeted metabolomic analyses indicated that supplementation with LBP-3 markedly reversed 18 of the 48 differential metabolites (mainly belonging to amino acids and organic acids) disturbed by DSS. Targeted metabolomics revealed that the lower levels of tryptophan, lysine, diiodothyronine, kynurenine, and betaine and higher levels of phenylalanine, leucine, glutamine, isoleucine, homoserine, ( S )-2-hydroxyglutarate, 2-isopropylmalic acid, ascorbic acid, gluconic acid, and taurine, which were caused by DSS induction, were reversed by LBP-3 treatment. In addition, pathway analysis showed that the pentose phosphate pathway, phenylalanine metabolism, ascorbate and aldarate metabolism, and phenylalanine, tyrosine and tryptophan biosynthesis were strongly affected by LBP-3. More importantly, the above amino acids, organic acids, and metabolic pathways changed by LBP-3 were correlated with the abundance of gut microbiota such as Turicibacter, Lactobacillus, Parasutterella, Odoribacter, Veillonella, Faecalibacterium, and Ruminococcaceae. This study advances our understanding of the interaction between the microbiome and metabolomics in DSS-induced chronic colitis after LBP-3 treatment.